Detection of nano- and micro-sized particles in routine biopsy material - pilot study - Jana Dvorackova; Hana Bielnikova; Jana Kukutschova; Pavlina Peikertova; Peter Filip; Karol Zelenik; Pavel Kominek; Magdalena Uvirova; Jana Pradna; Zuzana Cermakova; Igor Dvoracek (Biomedical Papers, 2015)
Background: Nanotechnology is receiving enormous funding. Very little however is known about the health dangers of this technology so far. Chronic tonsillitis is one of a number of diseases called idiopathic. Among other factors, the tonsils are exposed to suspended particles in inhaled air including nano particles. The objective of this study was to detect and evaluate metallic particles in human tonsil tissue diagnosed with chronic tonsillitis and in amniotic fluid as a comparison. Methods: . Scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDX) was used for identification of solid particles in a total of 64 samples of routinely analyzed biopsy and cytologic material. Results: Almost all samples were found to contain solid particles of various metals. The most frequent, regardless of diagnosis, were iron, chromium, nickel and aluminium. The size, determined using SEM, varied from around 500 nm to 25 µm. The majority formed aggregates of several micrometers in size but there were a significant number of smaller (sub-micrometer or nano-sized) particles present. The incidence of metallic particles was similar in child and adult tissues. The difference was in composition: the presence of several metals in adults was due to occupational exposure. Conclusions: The presence of metallic particles in pathologically altered tissues may signal an alternative causation of some diseases. The ethiopathogenic explanation of these diseases associated with the presence of nano-sized particles in the organism has emerged into a new field of pathology, nanopathology.